Proceedings of the First Workshop on Hot Topics in Software Defined Networks 2012
DOI: 10.1145/2342441.2342447
|View full text |Cite
|
Sign up to set email alerts
|

Hey, you darned counters!

Abstract: Software-Defined Networking (SDN) gains much of its value through the use of central controllers with global views of dynamic network state. To support a global view, SDN protocols, such as OpenFlow, expose several counters for each flow-table rule. These counters must be maintained by the data plane, which is typically implemented in hardware as an ASIC. ASIC-based counters are inflexible, and cannot easily be modified to compute novel metrics.These counters do not need to be on the ASIC. If the ASIC data pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 8 publications
(9 reference statements)
0
30
0
Order By: Relevance
“…While targeting the data plane, proposals such as DevoFlow [416] and Software-Defined Counters (SDC) [432] actually reduce the overhead of the control plane by delegating some work to the forwarding devices. For instance, instead of requesting a decision from the controller for every flow, switches can selectively identify the flows (e.g., elephant flows) that may need higherlevel decisions from the control plane applications.…”
Section: Scalabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…While targeting the data plane, proposals such as DevoFlow [416] and Software-Defined Counters (SDC) [432] actually reduce the overhead of the control plane by delegating some work to the forwarding devices. For instance, instead of requesting a decision from the controller for every flow, switches can selectively identify the flows (e.g., elephant flows) that may need higherlevel decisions from the control plane applications.…”
Section: Scalabilitymentioning
confidence: 99%
“…SDCs [432] data plane Software-Defined Counters reduce the control plane overhead -Remove counters from the ASIC to a general purpose CPU, improving programmability.…”
Section: 2mmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, each router would need to report their average queue length to the RVSDN controller. It has been shown that statistic gathering is an expensive operation on the routers and switches [16]. More research is needed to determine if this method is cost effective.…”
Section: Related Workmentioning
confidence: 99%